The dominance of apprenticeships in the German VET system and its implications for Europeanisation : a comparative view in the context of the EQF and the European LLL strategy - Deissinger, Thomas [Verfasser]; Heine, Robin [Verfasser]; Ott, Mariska [Verfasser] (My University, 2011)
"Germany's apprenticeship system is and has always been considered to be the major sub-system of VET. In this context, the debate circling around the European and German Qualifications Framework (EQF and DQR) has become one of the central issues of VET research and policy. Tasks take on a concrete shape if (a) a serious approach is adopted towards the ideas underlying the European Qualifications Framework; and (b) if consideration is given to the 'construction sites' typical for the German VET system as a whole. This paper intends to sharpen VET policy awareness for the problem of dealing with those unresolved German VET issues within the context of the development of the DQR. A comparative view includes Austria and France as two countries with diverging learning cultures in VET from the German case, but obviously with more 'European' imprints within their respective VET systems. It can be shown that there is an interrelation between the attention apprenticeships as such receive against the background of European ideas such as 'progression', 'permeability' and 'lifelong learning' (LLL), including the implementation and use of 'hybrid qualifications'." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 1.3.4 Doppelqualifizierende Bildungsgänge; S 1.4 Hochschulbildung; S 2.3 Berufsbildungspolitik; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsausbildung; Duales System; Europäische Integration; Europäischer Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Doppelqualifikation; Dualer Studiengang; Berufsbildungspolitik; Bildungsreform; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Frankreich